Perlindungan Hukum terhadap Peserta Program Makan Bergizi Gratis Perspektif Maqāṣid al-Syarī‘ah - Muhammad Kharuddin; Zulham (AL-SULTHANIYAH, 2026)
The Free Nutritious Meal Program (MBG) is a national policy aimed at fulfilling children’s nutritional needs. However, its implementation has raised serious concerns, including food poisoning incidents. These issues indicate weaknesses in preventive legal protection, particularly in ex ante supervision. This study aims to analyze preventive legal protection in the implementation of MBG and to formulate reinforcement strategies based on Indonesian positive law and maqāṣid al-syarī‘ah. This research employs normative legal research using statutory and maqāṣid al-syarī‘ah approaches through the analysis of primary and secondary legal materials. The findings reveal that although the regulatory framework is relatively comprehensive, preventive supervision remains ineffective due to limited institutional capacity. This study recommends mandatory Standard Operating Procedures (SOPs) on food safety, nutritional standards, and halal assurance, along with a compliance labeling system, to strengthen preventive legal protection.